Integrating Islamic Moral Values into Holistic Education: A Systematic Character Development Model in Indonesian Junior High Schools - Ifa Maulida; Benny Prasetiya; Muhammad Faizal A Ghanib (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to examine how Islamic moral values are systematically integrated into holistic education through a structured character development model in Indonesian junior high schools. The research focuses on SMP Muhammadiyah 1 and SMP Integral Hidayatullah Probolinggo, two schools that formally embed value-based programs across curricular and extracurricular activities. Employing a qualitative multi-site case study design, data were collected through in-depth interviews with teachers, students, parents, and community representatives, sustained classroom and ritual observations, and document analysis. The data were analyzed using reflexive thematic analysis to identify patterns of moral internalization and contextual influences. The findings reveal four interconnected mechanisms of internalization: (1) classroom-based value reinforcement embedded across subjects; (2) ritualized religious habituation through shalat dhuha, Qur’an recitation, and halaqah mentoring; (3) everyday moral habits shaped by peer influence; and (4) cross-context reinforcement among school, family, and community. The study also identifies three forms of student resistance: silent compliance, moral fatigue, and peer counter-culture. The novelty of this research lies in operationalizing a layered and ecological character development model that integrates curricular, ritual, social, and contextual dimensions within a unified framework. The study contributes theoretically by bridging integrative-curricular, habitualization, experiential, and ecological approaches, and practically by offering a replicable model for sustainable Islamic moral education at the secondary school level.